The role of metabolic disorders in the pathogenesis of intrahepatic cholestasis of pregnancy - Menżyk, Tomasz; Bator, Martyna; Derra, Aleksandra; Kierach, Rafał; Kukla, Michał (Clinical and Experimental Hepatology, 2018)
Intrahepatic cholestasis of pregnancy (ICP) is a pregnancy-specific liver disorder which typically commences in the late second or third trimester and resolves within 48 hours after delivery. It is characterized by mild to severe pruritus, without any specific dermatologic features, elevated liver enzymes and increased serum bile acids (BA). The etiology of ICP is still not completely explicit. Pathogenesis includes a combination of hormonal and environmental factors superimposing on a genetic predisposition. During recent years increasingly ICP is recognized to be associated with an abnormal metabolic profile, including glucose intolerance and dyslipidemia, although it is considered to be secondary to maternal aberrant BA homeostasis. This article reviews the recent literature data and current concepts for ICP, with emphasis on a possibility of metabolic disorders being primary causative factors in ICP pathogenesis.